Корпоративна соціальна відповідальність у контексті перспектив соціальної політики України - Карлін, М.І.; Звонар, В.П. (Інститут демографії та соціальних досліджень НАН України, 2007)
В статье выявлены основные социальные и экономические предпосылки активизации корпоративной социальной ответственности в Украине, ее теоретическое и практическое значение; основные всеукраинские и региональные тенденции корпоративной социальной ответственности, а также очерчена ее перспектива в контексте потребностей социальной политики Украины The article produces a global view upon the main social and economic prerequisites for activation of corporate social responsibility in Ukraine, theoretical and practical value of corporate social responsibility’s conception, generalization of world’s experience, Ukraine’s national and regional today trends of corporate social responsibility’s development and its vistas with regard to social policy of Ukraine.